A59 A RARE PRESENTATION OF COLLAGENOUS GASTRODUODENITIS WITH 10 YEAR FOLLOW UP. (21st February 2022) - Akhtar, N H; Akhtar, D; Tam, L; Nimmo, M; Donnellan, F
Abstract: Background: Collagenous gastritis(CG) is a rare form of gastritis defined histologically by the presence of >10um of subepithelial surface collagen deposition. CG can further be categorized in childhood onset CG and adult onset CG. The prevalence of childhood CG is 2.1/100, 000 in children aged younger than 18. Adult onset CG remains a rare entity. Here, we describe a rare presentation of collagenous gastroduodenitis in an adult patient and the interval progression over a 10 year period. Aims: To increase awareness of a rare condition with limited data on available treatment modalities and clinical outcomes in adults. Methods: Case Report Results: A 35 year old female with no past medical history presented with worsening fatigue and increased shortness of breath with no overt gastrointestinal bleeding symptoms. There was no previous history of radiation exposure or family history of autoimmune disease. Laboratory investigations revealed iron deficiency anemia with a hemoglobin of 69 and a ferritin of 11. TTG serology and anti-parietal antibody was also negative. Esophagogastroduodenoscopy biopsies confirmed the diagnosis of collagenous gastritis localized to the gastric body with the presence of acute and chronic inflammatory changes. The patient was started on proton pump inhibitor therapy. In the interval period, the patient denies any new onset of gastrointestinal symptoms other than occasional heartburn. She remains iron deficient and requires regular iron infusions. Follow up endoscopy 10 years later now demonstrates diffuse mucosal abnormalities with a nodular contour involving the entire stomach and extending into the duodenal bulb. Biopsies showed features compatible with collagenous gastroduodenitis with active inflammation and pyloric metaplasia(Figure 1). There was atrophy of the stomach mucosa with no parietal cells identified and no endocrine hyperplasia. Immunostaining for Helicobacter pylori was negative. Flexible sigmoidoscopy was also performed revealing endoscopically normal colonic mucosa to the descending colon. Conclusions: CG is a rare disease entity with unclear pathogenesis. Multiple case reports describe some association with autoimmune disease such as celiac disease. To date, no standard treatment has been identified for the management of CG. CG presents endoscopically with nodular changes, mucosal atrophy and collagen deposition. Over time, adult onset CG can progress to involve the entire stomach. Clinically, adult onset CG usually presents with a diarrhea predominant phenotype with associated collagenous colitis. Treatment modalities that have been trialed include PPI, corticosteroids, sucralfate, azathioprine, 5-aminosalicylates, iron supplementation and hypoallergenic diets. Here we describe a rare presentation of collagenous gastroduodenitis and subsequent 10 year follow up in order to better understand this disease entity. Funding Agencies: None